Penerapan Model Pembelajaran Kooperatif Tipe Stad Dalam Meningkatkan Hasil Belajar Ekonomi Di Kelas XI SMA Negeri 10 Bulukumba - nelly, nelly (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
This study aims to determine the economic learning outcomes of students by using the STAD Cooperative Learning Model (Student Teams Achievement Division). The method used is a classroom action research approach that takes place in two cycles. Data are analyzed quantitatively and qualitatively. The results of the study showed that the learning outcomes of students in the material analyzing employment problems in Indonesia experienced an increase. This is based on the results of the analysis carried out, obtained classical completeness that is 53.33 percent increased to 86.67 percent